Nothing in This World Is Indifferent to Us': The Primacy of Encounter and the Intersubjectivity of Nature - Robertson, Anna (Lumen et Vita, 2015)
“We’re moving from one plane of reality to another,” says Terry Tempest Williams in an interview with Yes! Magazine, “and what is required of us is spiritual.” Many people alive in the United States today have grown up bombarded by the seemingly futile refrain that if we don’t cut back on x (activity) in y (years), z (catastrophe) will ensue – with x becoming broader in scope, y becoming smaller in number, and z becoming more horrific with each passing year. Among the natural responses to such daunting and repetitive premonitions are anxiety and anguish: “Accept the anxiety, embrace the deeper anguish,” suggests Robert Jensen, “and then get apocalyptic.” Drawing upon Laudato si, liberation theology, and eco psychology, this paper argues for the importance of encounters (increasingly scarce) with the natural world, human and other-than-human, as a necessary spiritual practice grounding a commitment to ecojustice in times which are indeed end times of sorts. In a consideration of theological anthropology, I suggest, along with ecopsychologist Will Adams, that our subjectivity is indeed an intersubjectivity, arising out of our ethical response to not only the human other but also the other-than-human. We are by nature relational beings, and we must remember that this relation is not only relevant in human-human relationships. Liberation theologians have articulated the foundational nature of the encounter with poor – an experience which at once inspires awe, evokes mercy, and demands action – in grounding liberative praxis. Likewise, the encounter with nature, when its intersubjectivity is considered, grounds a praxis of ecojustice. Finally, understanding apocalypse in its etymological sense as “unveiling,” I argue for the role of the apocalyptic imagination, in making possible sustained exposure to such encounters, which entail both joy and despair. “Expect the end of the world,” writes Wendell Berry, “Be joyful though you have considered all the facts…Practice resurrection.”